A Study on Nishida Kitaro's Cross-Cultural Aesthetic Perspective in the Context of Globalization 3.0 (Journal of Global Arts Studies, 2026)
Background: In the era of Globalization 3.0, characterized by the deep integration of information technology and cultural exchange, the proliferation and diversity of cross-cultural art have become prominent. The philosophy of Japanese thinker Nishida Kitaro, particularly his concepts of “pure experience” and “logic of place,” offers a unique Eastern perspective for understanding cross-cultural aesthetics. Objective: This study aims to explore how Nishida’s philosophy provides theoretical support for cross-cultural aesthetics in the context of globalization and to analyze its implications for contemporary art practices. Methods: The research uses literature analysis and comparative study to examine Nishida’s key concepts like “absolute nothingness” and “place” in the context of Globalization 3.0. It also compares his ideas with Western aesthetic theories, such as Heidegger and Merleau-Ponty’s phenomenological aesthetics, to identify their similarities and differences. Results: The findings show that Nishida’s “logic of place” promotes cultural integration through mutual inclusivity and dynamic interaction. His “pure experience” concept unifies individuals and collectives, as well as subjects and objects, in art. His philosophy addresses cultural homogenization and supports cultural diversity in art. Conclusion: The study concludes that Nishida Kitaro’s cross-cultural aesthetic perspective enriches contemporary art theory and provides insights for cultural exchange and artistic innovation in Globalization 3.0. This perspective is valuable for global cultural dialogue and cross-cultural artistic practices.
Keywords: Globalization 3.0; Nishida Kitaro; Cross-Cultural Art; Logic of Place